Introduction: the power of example. (May 2015) - Højer, Lars; Bandak, Andreas; BANDAK, ANDREAS; HØJER, LARS
<x xml:space="preserve">Abstract</x> It is the contention of this introduction that examples are important prisms through which both reality and anthropological analysis are thought and, equally importantly, reconfigured. The aim of the introduction is to redress the theoretical disregard for exemplification by exploring the persuasive and evocative power – positive and negative – of 'examples' in social and academic life while also proposing exemplification as a distinct anthropological way of theorizing. Such theorizing points to a 'lateral' rethinking of the relation between the particular and the general. Our central argument is that examples highlight the precarious tension between the example as 'example' and the example as 'exemplar'. All contributions to this special issue, in one way or another, explore this tension between the unruliness of examples and the stability‐enhancing power of exemplarity. The introduction further proposes that the example serves to confuse ontological divides, such as the one between theory and ethnography, and also draws attention to the fact that theory is as much suggestive as descriptive.